Math Challenge Card Game Method (Medkit. Id) for Learning Basic Multiplications for Junior High School Students Guided by The Nusa Educator Community - Huda, Haifa Salsabila; Tutazqiyah, Aldira Dina; Yani, Mely Indri; Aruba, Fitria Maharani Siti; Fitri, Resfa (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This research aims to determine the effect of using the Math Challenge Card (Mathkit. id) card game method in learning multiplication on students assisted by the Nusa Educator Community. Method: This research used 25 students assisted by the Nusa Educators Community aged 12-17. The data is in the form of post-test scores, which will be compared with students’ pre-tests during research at each game level. Practical Applications: This card game method can be used to learn multiplication, especially for students who have not memorized basic multiplication operations. Conclusion: The research results showed an increase in the post-test skills scores compared to the students’ pre-test. The increase in the score at level 1 was 23%; at level 2, it was 31%, and the average maths quiz score was 85. This indicates that the Math Challenge Card (Mathkit. id) game method effectively improves students’ multiplication abilities.